2016
DOI: 10.1016/j.amepre.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes to Early Middle Age Linked With Childhood Residential Mobility

Abstract: IntroductionLinks between childhood residential mobility and multiple adverse outcomes through to maturity, and effect modification of these associations by familial SES, are incompletely understood.MethodsA national cohort of people born in Denmark in 1971–1997 were followed from their 15th birthdays until their early forties (N=1,475,030). Residential moves during each age year between birth and age 14 years were examined, with follow-up to 2013. Incidence rate ratios for attempted suicide, violent criminali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
5
34
1
Order By: Relevance
“…However, whilst remaining cautious about making causal inferences from our observations, a speculative potential alternative explanation is that separation from both parents during early adolescence is a particularly harmful to the wellbeing of these young people, at a crucial time in their development as they move toward making the transition from childhood to adulthood. Another possible interpretation is that separation from both parents at this age is likely to entail residential relocation, which we have previously reported as being strongly linked with elevated risk for these two adverse outcomes ( Webb et al, 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…However, whilst remaining cautious about making causal inferences from our observations, a speculative potential alternative explanation is that separation from both parents during early adolescence is a particularly harmful to the wellbeing of these young people, at a crucial time in their development as they move toward making the transition from childhood to adulthood. Another possible interpretation is that separation from both parents at this age is likely to entail residential relocation, which we have previously reported as being strongly linked with elevated risk for these two adverse outcomes ( Webb et al, 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…This result suggests that any environmental, psychosocial, or sociocultural influences linked with low family income were likely to have a bigger impact on offspring's externalised than internalised aggressive behaviours. Studies examining other exposures such as parental psychopathology 11 and frequent residential mobility during adolescence 31 have also reported stronger links for violent offending than for self-harm.…”
Section: Self-harmmentioning
confidence: 99%
“…Childhood mobility and physical abuse were significantly correlated in this study. Childhood mobility has been shown to increase the risk of suicide, violence and psychopathology [33]. It has been suggested that frequent childhood mobility is more common among individuals with low socioeconomic status and may be a sign of family malfunction [34].…”
Section: Discussionmentioning
confidence: 99%